Detection of alpha-foetoprotein messenger RNA in human hepatocellular carcinoma and hepatoblastoma tissue. - Di Bisceglie, A. M. (1986)
Alpha-foetoprotein (AFP) synthesis, although repressed in normal adults, is increased in the majority of patients with hepatocellular carcinoma (HCC). We have investigated whether active transcription of the AFP gene may explain raised serum AFP concentrations in patients with HCC and hepatoblastoma by assaying human tumour and non-neoplastic tissue by molecular hybridization for the presence of mRNA encoding AFP. Ten operative HCC and six autopsy HCC specimens, two HCC cell lines, and one hepatoblastoma specimen were examined. Total cellular RNA and poly-(A)+ RNA were extracted and AFP mRNA sequences sought by dot-blot and Northern blot hybridisation to a human cDNA AFP probe. Cellular AFP was localised by avidin-biotin staining. AFP mRNA was detected in 8/10 operative specimens, as well as PLC/PRF/5 nude mouse tumours. Weaker hybridization was detected in 4/6 autopsy specimens. Signals of comparable intensity to that in operative tumours were detected in non-neoplastic tissue of 6 patients. AFP mRNA from nude mouse tumours migrated as a 20S discrete band on agarose gel electrophoresis, whereas a more complex hybridization pattern was evident in human tumours. Positive cytoplasmic immuno-staining for AFP was observed in 4 tumours and 2 corresponding non-neoplastic specimens and in a HCC cell line. In non-neoplastic liver, AFP was localised in cells that appeared dysplastic. Thus steady-state levels of AFP mRNA are detectable in human HCC tissue and surrounding non-neoplastic liver. These findings may prove pertinent to an understanding of the genetic expression of AFP in malignant hepatocytes, and the sequence of events leading to uncontrolled cellular proliferation.